2009
DOI: 10.1007/s10826-009-9256-z
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Parenting Style and Personality: Direct Influence or Mediation?

Abstract: In order to examine the relationships between parenting styles and personality traits over generations, a cross-sectional questionnaire study was conducted for fathers and mothers of school-age children of grades 5-9. The parenting styles measured by the Parental Bonding Instrument (PBI) and the personality traits measured by the Temperament and Character Inventory (TCI) were correlated within and between the consecutive generations (the grandparents and the parents for the PBI and the parents and the children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 80 publications
10
56
0
2
Order By: Relevance
“…The results of the present study, taken as a whole, support the empirical evidence suggesting that parental lifestyle or personality are related to parenting behaviors or styles (e.g. Huver et al, 2009;Kitamura et al, 2009;Metsapelto & Pulkinnen, 2003;Lundberg et al, 2000, etc. ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of the present study, taken as a whole, support the empirical evidence suggesting that parental lifestyle or personality are related to parenting behaviors or styles (e.g. Huver et al, 2009;Kitamura et al, 2009;Metsapelto & Pulkinnen, 2003;Lundberg et al, 2000, etc. ).…”
Section: Discussionsupporting
confidence: 88%
“…Numerous research studies related to the connection between parents' personality and parenting have continually supported and suggested the signi cance of personality as an important variable in predicting a variety of parenting behaviors (Desjardins et al, 2008;De Haan, Prinzie & Dekovic, 2009;Huver, Otten, de Vries & Engels, 2009;Kitamura, Shikai, Uji, Hiramura, Tanaksa & Shono, 2009;Kochanska et al, 1997;Metsapelto & Pulkinnen, 2003;Latzman, Elkovitch & Clark, 2009;Lundberg, Perris & Adolfson, 2000;Oliver, Wright Guerin & Co man, 2009;Olsen, Martin & Halverson, 1999). The majority of these studies have focused on exploring the relationships of parenting behaviors and the ve-trait personality model.…”
Section: Research On Personality and Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although parents and children can reciprocally affect each other, most findings suggest that parenting style influences the development of children's behavior and traits, rather than children's psychological tendencies affecting parenting style (e.g., Aguilar 1998;Kitamura et al 2009;Lytton 1990;Patterson 1982). In this vein, Bornstein's (1992) review of developmental, social, and clinical studies of dependency concluded that overprotective, authoritarian parenting leads to child dependency and eventually to a variety of problems (e.g., depression, alcohol use and dependence, tobacco dependence, obesity, and eating disorders).…”
Section: Parenting Styles and Children's Psychological Tendenciesmentioning
confidence: 99%
“…Such a direct mechanism of influence has been held to explain the continuity that has been observed in empirical studies (Putallaz et al, 1998). A mediational model involving interpersonal style, parenting beliefs, psychological state and social participation has also been cited as a factor explaining continuity in parenting behaviour across generations (Chen & Kaplan, 2001;Kerr et al, 2009;Kitamura et al, 2009;Putallaz et al, 1998). Very recently, epigenetic effects have been suspected to account for the transmission of parenting from one generation to the next.…”
Section: Introductionmentioning
confidence: 99%